Schools of jurisprudence and influences on jurisprudence in Vietnam - Pham, Hong Thai (Đại học Quốc gia Hà Nội, 2020)
The article summaries several schools of law over the world and gives some comments about the influence of these schools as well as the Soviet Jurisprudence on Vietnamese legal theory and laws, especially Vietnamese Constitutional laws. The author assumes that the current legal theory and laws of Vietnam reflect the transplantation of many different schools of legal science. That derives partly from the historical context but is also suitable for small countries like Vietnam in the context of global integration today. The author will try to explain the objective and subjective historical factors that affect these developments. On that basis, the author will identify some of the challenges and demands for innovating legal science in accordance with the current context in Vietnam.